Risco de quedas, mobilidade funcional e nível de atividade física de idosas institucionalizadas em São Luís - MA - CARDOSO, Rosinara de Sousa (2021)
Aging affects basic cognitive and motor functions, decreasing balance and functional mobility, which can lead to an increased risk of falls in the elderly. Some elderly people depend on the support and care of the Family, however, due to cultural, socioeconomic and/or instability in the Family environment, they sometimes need to resort to the care of a Long Term Institution (ILPI). The aim of this study was to analyze the risk of falls, functional mobility and the level of physical activity of elderly women residing in a ILPI in São Luís, Maranhão. Twenty elderly women aged over 60 years, participated in the research, 10 in each group: institutionalized (GI) and non-institutionalized (GNI). Participation in the research was subject to signing the Informed Consent Form, expressing interest in being a volunteer. The assessment instruments were: a) Anamnesis (age, weight, height, presence of falls in the last year); b) Mini Mental State Examination (MMSE); c) International Physical Activity Questionnaire (IPAQ) long version for the elderly; d) Berg scale for risk of falls and balance; e) Timed Up and Go (TUG) test of functional mobility. The hypothesis raised was that institutionalized elderly women would have worse scores in tests of balance, risk of falls and functional mobility than non institutionalized ones, as institutionalization can reduce several daily tasks, contributing to the increase in inactivity. Institutionalized elderly (mean age 75 ± 7,12 years) and non institutionalized elderly women (mean age 75,20± 7,27) had similar scores on the MMSE with a mean of 27,50 ± 1,43 in GI and 27,70 ± 1,49 in the GNI. Four elderly women from GI reported the presence of falls in the last year, and the number of falls ranged from one to three, with two elderly women reporting two falls, in the GNI, two elderly women reported one fall and two falls. With the results of the IPAQ in the GI, two elderly women were classified as sedentary and eight as irregular active, in the GNI two were classified as sedentary, five as irregularly active and three as active. The average score on the Berg scale was 43 in the GI and 52 in the GNI and in the TUG test 15 in the GI and 9 in the GNI. It can be concluded that institutionalized elderly women presented greater balance déficit and a lower level of functional mobility, reported a greater number of falls, and obtained a lower level of physical activity When compared to non institutionalized elderly women, notig the absence of active elderly women in the institution.